Zinc therapy for different causes of diarrhea - Hafaz Zakky Abdillah; Supriatmo Supriatmo; Melda Deliana; Selvi Nafianti; Atan Baas Sinuhaji (Indonesian Pediatric Society, 2013)
Background The incidence of diarrhea in Indonesia has declinedin the past five years. In spite of the increasing number of studieson the treatment for acute diarrhea, especially the use of zinc,it is not known if bacterial vs. non-bacterial etiology makes adifference in the reduction of severity of acute diarrhea in childrenon zinc therapy.Objective To assess the effect of zinc therapy in reducing theseverity of acute bacterial and non-bacterial diarrhea.Methods We performed a cross-sectional study in the SecanggangDistrict, Lan gkat Regen cy of North Sumat era, from Augustto November 2009 in children aged 2 months to 14 years .Microscopic stool examination s were undertaken to separatesubjects into the acute bacterial or non-bacterial diarrhea groups.Both groups received 10 mg/day ofzinc sulphate for subjects aged<6 months or 20 mg/day for those aged 2:6 months for 10 days.Measurement of disease severity was based on the frequency ofdiarrhea (times/day) and the duration of diarrhea (hours) afterinitial drug consumption . We performed indepen dent T test forstatistical an alysis.Results Sixty-two children participated in this study, with 31children in the acute bacterial group, and the remainder in thenon-bacterial group. There were no significant differences betweenthe two gro ups in frequency of diarrhea (2 .61 vs 2.70 times/day,respectively, P=0.27) or in duration of diarrhea (63.39 vs 66.68hours, respectively, P= 0.06) .Conclusion Zinc is not more effective in reducing the severityof acute bacterial diarrhea compared to non-bacterial diarrhea inchildren.